DETERMINANTS OF MOTIVATION AMONG HEALTHCARE WORKERS IN MALAYSIA: A SYSTEMATIC REVIEW - Zubair, Nur Fadhilah; Ayub, Nor Aliya; Daud, Faiz; Mohammed Nawi, Azmawati; Hod, Rozita (Malaysian Journal of Public Health Medicine, 2025)
Healthcare worker motivation is essential for job satisfaction, engagement, and the effective operation of healthcare systems. In Malaysia, challenges such as workforce shortages, public-private disparities, and brain drain significantly impact motivation and retention. This systematic review identifies the key determinants of healthcare worker motivation in Malaysia. A systematic search was conducted across several databases up till December 2024. Keywords included terms related to healthcare workers, motivation, and the Malaysian healthcare context. Data extraction followed a standardized protocol, and the methodological quality of studies was assessed using the Mixed Methods Appraisal Tool (MMAT), and data synthesis followed a convergent integrated design. Intrinsic motivators such as personal beliefs, task significance, and growth opportunities were critical in influencing motivation. Group-level factors, including teamwork, supervisor support was highly valued, reflecting Malaysia’s collectivist cultural values. Organizational barriers such as staffing shortages, high workloads, and public-private pay disparities posed significant challenges to motivation. Financial incentives were acknowledged, where dissatisfaction with salary increment were prevalent. Motivated healthcare workers exhibited higher job satisfaction, organizational commitment, and engagement, contributing to better patient care and retention. This review underscores the need for structured career pathways, equitable remuneration, and supportive work environments to address motivational challenges. Team-building activities, professional development opportunities, and community recognition were recommended to enhance both individual and group motivation. Future research should explore culturally specific motivational factors using mixed method and longitudinal designs to develop sustainable workforce resilience. Enhancing healthcare worker motivation is critical for overcoming workforce challenges and ensuring high-quality, sustainable care in Malaysia.